Business and intellectual property: protect your ideas - "Agarwal, Anurag K." (Noida, 2010)
Business and Intellectual Property reflects on the future of IP in the age of new media and shows how - in a rapidly changing business field$1 (Bmanagers and decision-makers need to be more perceptive, agile and vigilant than ever before. Drawing on contemporary business affairs and strategies, it explores the nature and scope of IP and the evolution of national laws and global agreements like the TRIPs to protect it. It also explores the measures (the use of patents, copyrights and trademarks) used by some of the biggest brands$1 (BCoke, MGM, 20th Century Fox, Microsoft, Harrods, Maruti, Tata$1 (Bto manage disputes and protect themselves.s
Keywords: Intellectual property-Business environment